ANALISIS PENGENDALIAN KUALITAS PRODUK BOX PANEL LISTRIK DENGAN METODE STATISTICAL PROCESS CONTROL (SPC) (Studi pada PT. Indra Cipta Sentosa Lestari) - Sudarsono, Esa Nandatri (Universitas Mercu Buana, 2024)
PT Indra Cipta Sentosa Lestari is a company engaged in the manufacture of electrical panel box. To maintain customer satisfaction, the company strives to produce the highest quality products. Competition that occurs in the industrial sector makes us always have to maintain the quality of the products produced. Because a good product quality will be able to fulfill the desires and needs of consumers, so it is very important for companies to always maintain product quality so that they can compete with other companies in order to maintain customer satisfaction. Therefore, companies must carry out continuous quality control activities for the products they produce. One of the causes of not achieving company goals is the quality of the products produced are not good. Less optimal use of production factors can lead to a decrease in the quality of the product produced. Data were collected by interview and observation methods, then analyzed using Statistical Process Control (SPC) tools. The results showed that based on the pareto diagram (pareto chart) made, it can be concluded that the highest level of damage was in the painting section, followed by the damage level in the bending section, welding section, and lastly in the assembling section of the total production of 726. From the fishbone diagram ) found that the material factors of machines, humans (employees), environment, and methods, are the causes of product defects.